2016
DOI: 10.1108/jsm-10-2014-0342
|View full text |Cite
|
Sign up to set email alerts
|

The effect of workplace incivility on service employee creativity: the mediating role of emotional exhaustion and intrinsic motivation

Abstract: Purpose This study aims to examine how workplace incivility (i.e. coworker and customer incivility) affects service employees’ creativity, specifically the way emotional exhaustion at work decreases their intrinsic motivation, and, in turn, damages service employees’ creativity. The purpose of this study, therefore, is to show the mechanism by which both coworker and customer incivility at work affects service employee creativity. Design/methodology/approach Service employees from a hotel in South Korea were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 89 publications
9
103
1
2
Order By: Relevance
“…Amabile, Hennessey, & Tighe, 1994;Amabile & Mueller, 2008;Carmeli, Reiter-Palmon, & Ziv, 2010;Shalley, Zhou, & Oldham, 2004) and some recent empirical evidence (e.g. Hannam & Narayan, 2015;Hur et al, 2016;Muñoz-Pascual, & Galende, 2017) have suggested that intrinsic motivation is a mediating construct between different variables and creative performance. Therefore, we propose the following:…”
Section: Figure 4 -Factors Affecting Job Attitudes As Reported In 12 mentioning
confidence: 99%
“…Amabile, Hennessey, & Tighe, 1994;Amabile & Mueller, 2008;Carmeli, Reiter-Palmon, & Ziv, 2010;Shalley, Zhou, & Oldham, 2004) and some recent empirical evidence (e.g. Hannam & Narayan, 2015;Hur et al, 2016;Muñoz-Pascual, & Galende, 2017) have suggested that intrinsic motivation is a mediating construct between different variables and creative performance. Therefore, we propose the following:…”
Section: Figure 4 -Factors Affecting Job Attitudes As Reported In 12 mentioning
confidence: 99%
“…Workplace incivility has been associated with unwanted outcomes such as high burnout, emotional exhaustion, negativity, workplace withdrawal, and intention to sabotage (e.g., Abubakar, Yazdian, et al, 2018;Cortina et al, 2001;Hur, Moon, & Jun, 2016); reduced performance and creativity (Arasli et al, 2018;Rahim & Cosby, 2016). The above said outcomes are distinct variables but shares several similarities with variables like employee cynicism, knowledge hiding behavior, job search behavior, and service innovative behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Porath and Erez () found incivility instigated by authority or a third party, or just an imagined incivility can reduce the target employees’ creativity by disrupting their cognitive processes. Within a service management context, Hur, Moon and Jun () found incivility from customers and co‐workers decreases service employees’ creativity through the sequentially mediating role of emotional exhaustion and intrinsic motivation. At team level, Sharifirad () suggested that supervisor incivility negatively affects team creative performance by weakening employees’ intention to share knowledge.…”
mentioning
confidence: 99%